Community Resilience Post-Pilkada Conflict to Supporting Social Sustainability in The Jakarta Area - Lusi Andriyani; Raja Faid El Shidqi; Luthfiyani Nurul Jannah; Mawar (Journal of Public Administration and Government, 2022)
The 2017 DKI Jakarta Pilkada presents an account of the political disputes that occurred, as well as the prevalence of racial and ethnic difficulties, which have long given rise to horizontal conflicts. This incident provided significant impetus to participate in attempts to strengthen community resilience as a result of social disputes generated by political events such as the Pilkada. The purpose of this research is to look at the resilience of the communities in DKI Jakarta during the Pilkada conflict mentioned above. This study employs a qualitative approach, as well as tools for locating data in documents and archives. Data from the field suggest that the exploitation of racial concerns by specific groups, as well as other issues such as intimidation, insults, and the sharing of inflammatory photographs and videos, contributed to the heightened severity of conflict in the 2017 Pilkada in DKI Jakarta. As a result, it is critical to enhance community resilience in three ways: build the resilience of an established social system, strengthen the community's responsiveness to internal and external changes through social capital building, and carry out social transformation through political education.